Religious Tourism and Rural Tourism, an Alternative for Development in Isolated Regions - Nuñez, Paula Gabriela (New Countryside, 2026)
This paper problematizes and critically examines rural development research carried out in Argentina, especially in the Andean region of northern Patagonia. The study focuses on the steppe, one of the nation’s most sparsely populated regions, adjacent to the Andean region, which is known for being one of Argentina’s most attractive natural tourist destinations. In this context, rural tourism is envisioned as a prospective development path, an aspiration stymied by significant infrastructure deficiencies. Furthermore, recent studies are beginning to reveal the deep religious roots in the foundations of local resilience. This encompasses the diverse religious landscape of the Mapuche people, the largest Indigenous group in the region, evangelical denominations, and Catholic practices. This article advances by highlighting how the recognition of resilience rooted in faith practices allows for rethinking tourism, designing attractions from a religious tourism perspective, and boosting the region’s production associated with possible rural tourism strategies, not as mass tourism, but as an endogenous development strategy based on living heritage with a community-based and community-controlled nature of the tourism practices. This proposal builds upon the pivotal role of women in both economic production and the preservation of faith. Through practices of faith, it is possible to explore the existence of underlying channels of contact that, while integrated into daily life, often remain overlooked. These channels make it possible to envision other futures, with greater sustainability in productive practices, diversified in terms of tourism, and increasingly socially significant as they become rooted in the faith of each place.